2020
DOI: 10.1007/s11517-020-02277-8
|View full text |Cite
|
Sign up to set email alerts
|

Apnea bradycardia detection based on new coupled hidden semi Markov model

Abstract: In this paper, a method for apnea bradycardia detection in preterm infants is presented based on coupled hidden semi Markov model (CHSMM). CHSMM is a generalization of Hidden Markov Models (HMM) used for modeling mutual interactions among different observations of a stochastic process through using finite number of hidden states with corresponding resting time. We introduce a new set of equations for CHSMM to be integrated in a detection algorithm. The detection algorithm was evaluated on a simulated data to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Heart rate alarms are currently the most reliable way to detect the cardio-respiratory events associated with prematurity. The choice of the fusion method has the advantage to be easy to implement and embeddable into devices with low computational resources, when compared to other more sophisticated methods 16 , 17 , 19 21 . Portet et al also observed a small improvement in the time delay for detection of bradycardia using a decision tree approach 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heart rate alarms are currently the most reliable way to detect the cardio-respiratory events associated with prematurity. The choice of the fusion method has the advantage to be easy to implement and embeddable into devices with low computational resources, when compared to other more sophisticated methods 16 , 17 , 19 21 . Portet et al also observed a small improvement in the time delay for detection of bradycardia using a decision tree approach 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Portet et al also observed a small improvement in the time delay for detection of bradycardia using a decision tree approach 20 . Our group has proposed a set of hidden and coupled semi-Markovian methods that also provide earlier detection delays with increased performance levels 16 , 17 , 21 . However, none of these works have evaluated performance sensitivity with respect to the different definitions of bradycardia and under real-life conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For simulated data, the proposed algorithm was able to detect the desired dynamics with 96.67% sensitivity and 98.98% specificity. e results show that the CHSMM-based algorithm is a robust tool for monitoring apnea remission in preterm infants [4]. Zhang started with the influence of cultural context on Chinese-English translation and discusses the context in Chinese-English translation combined with practical work experience as well as the understanding and practice of translation activities from the perspective of cultural translation.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, episodes of apnea-bradycardia have been observed in various studies [32], [33], including one using Coupled Hidden Semi-Markov Models (CHSMM) [34] and another employing layered HMMs, both based on electrocardiographic data. This detection contributes to the rapid diagnosis of this phenomenon in premature infants, a population where it occurs most frequently, thus avoiding neurological developmental issues and mortality [32], [33], [35].…”
Section: Research Backgroundmentioning
confidence: 99%